Owner-occupied housing costs and bias in the Irish consumer price index - Colm McCarthy (University College Dublin, UCD School of Economics, 2007)
The treatment of owner-occupied housing costs is a recurring problem in the construction of consumer price indices, and there are competing methodologies. In the most widely-used Irish index, the Payments Approach, which attaches a weight to a term involving historical house prices and an interest rate, is used to measure these costs. It is argued that this has resulted in a substantial over-statement of inflation in recent quarters, and that the over-statement will continue for some time. The Irish version of Eurostat's Harmonised Index of Consumer Prices, recently running well below the CPI, is a more reliable guide. Few national statistical offices use the Payments Approach, and it is argued that the procedure used in Ireland should be reviewed.
Keywords: C43; C82; D12; E31; 330; Consumer Price Index; Cost of Living Index; Payment Approach; Owner-Occupied Housing; Lebenshaltungsindex; Wohneigentum; Wohnkosten; Schätzung; Irland